Analysis of placental pathology and fetal outcome - Ramachandran, Amrutha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: A careful examination of placenta along with microscopic study may frequently point to the cause of perinatal death. The American College of Pathologists has provided guidelines for the examination of placenta. Aim of this study was to illustrate the gross and histopathological changes in placenta in certain normal and abnormal pregnancies and to analyse the relationship of placental pathology with fetal outcome. Methods: A prospective study of 120 deliveries at a tertiary teaching centre in India. Each placenta was studied macroscopically and sent to the pathology department for histological examination. The study included placentas of normal pregnancies and those with maternal high-risk features. The placenta was fixed in formalin and 6 sections were taken. The paraffin sections were studied for vessel wall thickening, infarction, villitis, chorioangiosis, calcification and intervillous hemorrhage. The primary outcome variables were fetal and neonatal morbidity. Abnormal fetal /neonatal events in each histological group were compared with the normal group using Ψ2 test for homogeneity. For cell frequencies less than 5, Fischer exact test was used. Results: Vessel wall thickening was demonstrated in 54/120 patients (45%). 7 out of 54 (12.96%) fetuses were still born in this group compared to 2/30 (6.67%) with normal histology (p value <0.05). Infarcts were demonstrated in 15/120 (12.5%). The occurrence of abnormal neonatal events in this group was significant p <0.01. Conclusions: Placental histological features of vessel wall thickening, and infarction is associated with abnormal fetal and neonatal outcome. Larger studies are required to establish the inference.